Modulation of gut microbiota: An emerging consequence in neonatal sepsis - Faiza Iqbal; Leslie Edward S. Lewis; N Siva; Vandana K E; Jayashree Purkayastha; Padmaja A. Shenoy (Clinical Epidemiology and Global Health, 2023)
Introduction: Billions of microorganisms reside in gut altering its homeostasis and leading to various diseases. The initial days of life are crucial for developing gut flora that helps in gut maturation and neonatal health. This review summarizes the evidence on seeding of neonatal gut microbiota, modulation of gut microbiota in neonatal sepsis, antimicrobial resistance, and role of probiotics or other therapies to re-establish altered microbiota. Conclusion: Gut microbiota regulates host physiological homeostasis mediators, including the gut barrier function, and disease susceptibility pathways. Maintenance or restoration of microbiota and metabolite composition may be a therapeutic or preventative target against critical illness.